2021
DOI: 10.48550/arxiv.2108.02738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time Delay Interferometry combinations as instrument noise monitors for LISA

Martina Muratore,
Daniele Vetrugno,
Stefano Vitale
et al.

Abstract: The LISA mission will likely be a signal dominated detector, such that one challenge is the separation of the different astrophysical sources, and to distinguish between them and the instrumental noise. One of the goals of LISA is to probe the early Universe by detecting stochastic GW backgrounds. As correlation with other detectors is not possible for LISA, discrimination of such a GW background from the instrumental noise requires a good estimate of the latter. To this purpose we have revisited Time Delay In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…If the performances of six test masses and optical benches and fully identical, the acceleration noise and optical path noise could be precisely characterized by three or fewer TDI channels [21][22][23]. However, in the realistic case, the performance of instruments on each spacecraft may differ from each other, and these noises should be characterized individually by combing multiple TDI outputs [24][25][26][27].…”
Section: References Therein]mentioning
confidence: 99%
“…If the performances of six test masses and optical benches and fully identical, the acceleration noise and optical path noise could be precisely characterized by three or fewer TDI channels [21][22][23]. However, in the realistic case, the performance of instruments on each spacecraft may differ from each other, and these noises should be characterized individually by combing multiple TDI outputs [24][25][26][27].…”
Section: References Therein]mentioning
confidence: 99%
“…Moreover, additional combinations of 14-links that were missing in the previous catalogue are reported in [6], where it is illustrated that the total number of combinations could be reduce to a subset of 28 of 16-links, 3 of 14-links and 3 of 12-links, if one considers as equal combinations that differ only by any permutations of satellites or a time reversal symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is often considered sufficient to use '0th generation' TDI (meaning three constant and equal arms) to perform data analysis, recent studies showed that neglecting the percent level static arm-length mismatches can in some cases bring large errors when modelling the instrument response to non-suppressed noises and GW signals [6]. On the other hand, considering three unequal arms was sufficient there to accurately predict the result of numerical simulations performed taking the full orbital dynamics into account.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations